2011
DOI: 10.1007/s11626-011-9423-6
|View full text |Cite
|
Sign up to set email alerts
|

Adult-type myogenesis of the frog Xenopus laevis specifically suppressed by notochord cells but promoted by spinal cord cells in vitro

Abstract: Larval-to-adult myogenic conversion occurs in the dorsal muscle but not in the tail muscle during Xenopus laevis metamorphosis. To know the mechanism for tail-specific suppression of adult myogenesis, response character was compared between adult myogenic cells (Ad-cells) and larval tail myogenic cells (La-cells) to a Sonic hedgehog (Shh) inhibitor, notochord (Nc) cells, and spinal cord (SC) cells in vitro. Cyclopamine, an Shh inhibitor, suppressed the differentiation of cultured Ad (but not La) cells, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…On the other hand, from the fact that tail muscle does not convert to adult type even though they contain AMS cells, it is conceivable that during metamorphosis the growth and differentiation of AMS cells is specifically activated in the trunk DM portions but suppressed in the tail DM portions. As to this spatial control, Yamane et al (2011) suggested the possibility that the trunk-specific adult myogenesis is regulated by two cell-interactive mechanisms: a promotion by spinal cord (SP) cells and a suppression by notochord (Nc) cells (see section 6).…”
Section: Cell Interaction 16mentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, from the fact that tail muscle does not convert to adult type even though they contain AMS cells, it is conceivable that during metamorphosis the growth and differentiation of AMS cells is specifically activated in the trunk DM portions but suppressed in the tail DM portions. As to this spatial control, Yamane et al (2011) suggested the possibility that the trunk-specific adult myogenesis is regulated by two cell-interactive mechanisms: a promotion by spinal cord (SP) cells and a suppression by notochord (Nc) cells (see section 6).…”
Section: Cell Interaction 16mentioning
confidence: 99%
“…Then, is there any regulation from cells (or tissues) other than myoblasts (or muscles) for the trunkspecific adult myogenesis? From this point of view, Yamane et al (2011) reported the importance of interaction between myogenic cells and non-myogenic cells (i.e. notochord and spinal cord cells) for the trunk specific adult muscle differentiation during X. laevis metamorphosis.…”
Section: Cell Interaction 20mentioning
confidence: 99%
See 3 more Smart Citations